2012
DOI: 10.1111/j.1574-6976.2011.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

From meadows to milk to mucosa – adaptation ofStreptococcusandLactococcusspecies to their nutritional environments

Abstract: Lactic acid bacteria (LAB) are indigenous to food-related habitats as well as associated with the mucosal surfaces of animals. The LAB family Streptococcaceae consists of the genera Lactococcus and Streptococcus. Members of the family include the industrially important species Lactococcus lactis, which has a long history safe use in the fermentative food industry, and the disease-causing streptococci Streptococcus pneumoniae and Streptococcus pyogenes. The central metabolic pathways of the Streptococcaceae fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 223 publications
(312 reference statements)
3
46
1
Order By: Relevance
“…The pneumococcus is a pathogen that occupies a very different ecological niche from the dairy LAB; hence, it is highly plausible that the regulation of these processes may differ. This view is supported not only by our results but also by those from studies with other related human pathogens, such as Streptococcus mutans and Streptococcus salivarius (35). A detailed understanding of the central metabolism and its subtle connections to pneumococcal virulence and pathogenesis is still missing.…”
Section: Discussionsupporting
confidence: 76%
“…The pneumococcus is a pathogen that occupies a very different ecological niche from the dairy LAB; hence, it is highly plausible that the regulation of these processes may differ. This view is supported not only by our results but also by those from studies with other related human pathogens, such as Streptococcus mutans and Streptococcus salivarius (35). A detailed understanding of the central metabolism and its subtle connections to pneumococcal virulence and pathogenesis is still missing.…”
Section: Discussionsupporting
confidence: 76%
“…The ADI pathway is responsible for the conversion of arginine to ornithine and the subsequent generation of 1 mol ATP per mol arginine (48). This pathway was induced in L. lactis KF147 in ATL as well as in other other lactococci during glucose starvation (38,49) and was repressed by CcpA in the presence of glucose (12,50). Evidence of glucose limitation during L. lactis KF147 growth in ATL is also supported in the L. lactis metabolomes, which showed that even though glucose was the most abundant sugar in ATL, it was nearly entirely consumed by strain KF147 within 8 h and hence not available to sustain L. lactis over longer periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Although the LAB species Lactococcus lactis is best studied for its role in dairy fermentations (12), this species is often associated with plants. Plants were originally regarded as the natural habitat of L. lactis (previously termed Streptococcus lactis) (13).…”
mentioning
confidence: 99%
“…Importantly, this approach shows how industry could develop entirely new starter cultures. Comparative genomics has also provided a means to better understand and assure the 'generally recognized as safe' status of LAB in dairy foods [21][22][23][24], and most notably, revealed species-specific and strainspecific blueprints for the cellular networks and enzymes that contribute to flavor development in aged cheese [8,25,26,27 ].…”
Section: Post-genomics Approaches To Lab Cheese Flavor Enhancementmentioning
confidence: 99%